The complete mitochondrial genome of the Azuma emmnion. (2nd January 2017) - Chen, Xuejie; Chen, Yadong; Yu, Mengjun; Sha, Zhenxia; Shan, Xiujuan
Abstract: The complete mitochondrial genome of the Azuma emmnion has been determined. The total length of a complete nucleotide sequence of the mitochondria is 16 522 bp, which contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and one D-loop region. Its nucleotide sequence and composition of A. emmnion mitochondrion was similar to most other vertebrates. Nucleotide base composition of mitochondrial genome was the following: 25.58% for A, 18.22% for G, 27.67% for C, 28.53% for T. The phylogenetic analysis result, which based on the complete mitogenomes of of A. emmnion and other 11 fish species, indicated that A. emmnion and Pholis crassispina clustered into one branch.